Outcome of Recurrent Glomerular Diseases after Renal Transplantation. (July 2018) - Aziz, Tahir; Mubarak, Muhammad; Rizvi, Adib
Abstract : Introduction: Recurrent glomerular diseases are important cause of graft dysfunction after renal transplant. It is associated with poor graft outcome as compared to other diseases leading to end stage renal failure. The purpose of our study was to determine the risk factors and the incidence of recurrence in post-transplant period as well as their impact on graft survival rates. Method: We retrospectively analysed 110 patients with glomerular diseases. Mean follow up was 5 yrs. The outcome was compared with patients without FSGS during the same period of study. Results: Between 2000 to 2015, 3962 live related renal transplants were performed in 3434 adults and 528 children. Out of these 110 had biopsy proven FSGS. 74 were male and 36 were female. Age ranged between 5 and 50 yrs. 15 % had recurrence of FSGS. They were subjected to plasmapheresis. 2% had complete remission while 9% developed ESRF. Rest of them had partial remission. During the same period rest of the patients without FSGS had 5 yr graft survival of 88%. While patients with FSGS had 5 yr graft survival of 70%. Conclusion: Glomerulonephritis is the primary cause of ESRF in 30% of renal transplant recipients. Indeed almost all forms of glomerulonephritis have been reported to recur after renal transplant, but the incidence and severity of clinical recurrence varies greatly according to the type of glomerular diseases.